Diabetes mellitus control in a large cohort of people with HIV in care-Washington, D.C. Issue 11 (2nd November 2021) - Wallace, David E.; Horberg, Michael A.; Benator, Debra A.; Greenberg, Alan E.; Castel, Amanda D.; Monroe, Anne K.; Happ, Lindsey Powers; ,
ABSTRACT: With more effective antiretroviral therapy (ART), people with HIV (PWH) are living longer and have more chronic diseases, including diabetes mellitus (DM). The prevalence of DM has been estimated in PWH previously, however there is less research regarding DM control. Our objectives were to determine the prevalence of DM and DM control and determine factors associated with DM control in a large urban cohort of PWH in care. We examined DC Cohort participants aged ≥18 years old to determine DM prevalence and to assess DM control (HbA1c measurement <7.0%). Demographic, clinical, and HIV-related factors associated with DM control were identified using multivariate logistic regression. The cohort of 5876 participants was predominantly male (71.3%), Non-Hispanic Black (78.1%) and had a median age of 52.0 years. DM prevalence was 17.4% (1023/5876). Among participants with recent HbA1c data available (39.9%) the proportion with DM control was 60.0% (245/408). In multivariate analysis, higher BMI (aOR: 0.47; 95% CI 0.28, 0.79) and use of non-insulin DM medication (aOR 0.43, 95% CI 0.25, 0.73) or insulin (aOR 0.010, 95% CI 0.04, 0.24) compared to no medication use. Our findings suggest that individuals on medication for their DM likely need enhanced support to reach their treatment goals.